Breast Ironing from the Perspective of Transcultural Nursing by Madeleine Leininger: A Narrative Review - Rosa M. Cárdaba-García; Veronica Velasco-Gonzalez; Inés Cárdaba-García; Lucía Pérez-Pérez; Carlos Durantez-Fernández; Alba Muñoz-del Caz; Raúl Soto-Cámara; Marta Evelia Aparicio-García; Miguel Madrigal; Inmaculada Pérez (Nursing Reports)
(1) Background: This article addresses the harmful traditional practice of breast ironing, which primarily affects girls and adolescents in several countries, particularly in Cameroon. The practice involves applying heat and pressure to developing breasts to delay their growth, with the goal of protecting girls from sexual abuse, early pregnancy, and forced marriages. While culturally accepted, breast ironing has severe physical, psychological, and social consequences, including damage to mammary glands, pain, infections, and potential long-term health complications. (2) Methods: A reflective analysis of the topic was conducted through a comprehensive search of various databases (PubMed, Scopus, Google Scholar, and CINAHL) following narrative review methodology. (3) Results: The practice is also examined through the lens of human rights and Madeleine Leininger’s transcultural nursing theory, which promotes respect for cultural traditions in healthcare. However, the authors question whether such a theory can justify practices that violate women’s physical integrity. (4) Conclusions: This study concludes that while cultural beliefs must be considered in healthcare, human rights and the elimination of violent practices, such as breast ironing, must take precedence. Educational campaigns and a more punitive approach in countries where this practice occurs are proposed as essential steps forward.